Olfactory dysfunction in COVID‐19, new insights from a cohort of 353 patients: The ANOSVID study. Issue 10 (14th June 2022) - Mercier, Julien; Osman, Molka; Bouiller, Kevin; Tipirdamaz, Can; Gendrin, Vincent; Chirouze, Catherine; Lepiller, Quentin; Bouvier, Elodie; Royer, Pierre‐Yves; Pierron, Alix; Toko, Lynda; Plantin, Julie; et al.
Abstract: Olfactory disorders (OD) pathogenesis, underlying conditions, and prognostic in coronavirus disease 2019 (COVID‐19) remain partially described. ANOSVID is a retrospective study in Nord Franche‐Comté Hospital (France) that included COVID‐19 patients from March 1 2020 to May 31 2020. The aim was to compare COVID‐19 patients with OD (OD group) and patients without OD (no‐OD group). A second analysis compared patients with anosmia (high OD group) and patients with hyposmia or no OD (low or no‐OD group). The OD group presented less cardiovascular and other respiratory diseases compared to the no‐OD group (odds ratio [OR] = 0.536 [0.293–0.981], p  = 0.041 and OR = 0.222 [0.056–0.874], p  = 0.037 respectively). Moreover, history of malignancy was less present in the high OD group compared with the low or no‐OD group (OR = 0.170 [0.064–0.455], p  < 0.001). The main associated symptoms (OR > 5) with OD were loss of taste (OR = 24.059 [13.474–42.959], p  = 0.000) and cacosmia (OR = 5.821 [2.246–15.085], p  < 0.001). Most of all ORs decreased in the second analysis, especially for general, digestive, and ENT symptoms. Only two ORs increased: headache (OR = 2.697 [1.746–4.167], p  < 0.001) and facial pain (OR = 2.901 [1.441–5.842], p  = 0.002). The high OD group had a higher creatinine clearance CKD than the low or no‐OD group (89.0 ± 21.1 vs. 81.0 ± 20.5, p  = 0.040). No significant difference was found concerning the virological, radiological, and severity criteria. OD patients seem to have less comorbidity, especially better cardiovascular and renal function. Associated symptoms with OD were mostly neurological symptoms. We did not find a significant relationship between OD and less severity in COVID‐19 possibly due to methodological bias.